PEMBERDAYAAN KOMUNITAS WIRAUSAHA MUDA BERBASIS CONTENT MARKETING DI PRUMPUNG TENGAH JAKARTA TIMUR - Tuti Widiastuti; Eli Jamilah Mihardja; Holila Hatta (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2021)
Young entrepreneurs are now seen as having the potential to become the backbone or support for the country's economy. The problems of young entrepreneurs are still closely related to the difficulty of marketing. One of the factors that causes the distribution of goods to be less widespread is because young entrepreneurs have not done online marketing. Empowerment of young entrepreneurs is believed to be able to provide more benefits to businesses. But how business actors can make it part of a strategy that supports businesses in their respective core activities and supply chains is still an obstacle. The solution offered in this service program is to provide training and assistance that focuses on improving the ability of young entrepreneurs in the field of marketing communication through the website. For this reason, several sub-discussions will lead to promotion through the website, improving product quality through innovation and the use of technology. This program is carried out with the aim of encouraging and increasing the productivity of the young entrepreneurial community in Prumpung, East Jakarta so that they have both hard skills and soft skills so that they are able to be economically and socially independent.